A Physics-Based Model for ESD Protection Devices With Open Base BJT Configuration - Mousavi, Seyed Mostafa; Yan, Xin; Asadi, Reza; Mousavi, Mehdi; Bub, Sergei; Holland, Steffen; Beetner, Daryl G. (2024 46th Annual EOS/ESD Symposium (EOS/ESD), 2024)
This paper presents a simplified physics-based model for deep-snapback transient voltage suppressor (TVS) devices with open base BJT configuration. The proposed model is able to capture quasistatic IV curve as well as the transient behavior of the TVS including the initial voltage peak and the device turn on delay. A comparison of simulation and measurement results show that the proposed model can predict the quasi-static and transient behavior of an ESD protection device.